The production of Physalis spp. seedlings grown under different-colored shade nets - Daniel Fernandes da Silva; Rafael Pio; Joyce Dória Rodrigues Soares; Paulyene Vieira Nogueira; Pedro Maranha Peche; Fabíola Villa (Acta Scientiarum. Agronomy, 2016)
The objective of this study was to evaluate the production of seedlings of Physalis L. species under different-colored shade nets. Four shade nets individually stained white, blue, red and black, all with 50% shading, were used in this study, and an additional  treatment (control) was used in which seedlings were grown in full sun. The study examined four species of Physalis, namely, P. peruviana, P. pubescens, P. minima and P. ixocarpa. The experiment followed a randomized block design with three blocks and 25 seeds per plot. The species were sown in styrofoam trays. Germination was monitored daily to calculate the Emergency Velocity Index (EVI) and stabilize the overall percentage of emergence. Height, stem diameter, number of leaves, leaf area index and dry mass of seedlings were assessed at 50 days after sowing. The study found that these species react differently to changes in the light spectrum. Seedlings of P. peruviana should be grown under a white or red shade net; of P. pubescens under a white or black shade net; of P. minima under a white, red or black shade net; and of P. ixocarpa under a white shade net. For all species, 50% shade should be used.